Incidence of type 2 diabetes in familial combined hyperlipidemia. Issue 1 (18th March 2020) - Brouwers, Martijn C G J; de Graaf, Jacqueline; Simons, Nynke; Meex, Steven; ten Doeschate, Sophie; van Heertum, Shadana; Heidemann, Britt; Luijten, Jim; de Boer, Douwe; Schaper, Nicolaas; Stehouwer, Coen D A; van Greevenbroek, Marleen M J
Abstract : Objective: Familial combined hyperlipidemia (FCHL) is common among survivors of a premature myocardial infarction. FCHL patients are characterized by visceral obesity, fatty liver, and insulin resistance. The aim of the present study was to determine the incidence and determinants of type 2 diabetes (T2D) in a longitudinal cohort of FCHL pedigrees. Research design and methods: FCHL patients, their unaffected relatives and spouses included in our baseline cohort in 1998–2005 (n=596) were re-invited to determine the incidence of self-reported T2D (that was confirmed by medical records), used as the primary outcome measure. The Fatty Liver Index (FLI) and Homeostasis Model Assessment Insulin Resistance (HOMA2-IR) were used as markers of fatty liver and insulin resistance, respectively. A subset of the original cohort underwent ultrasound of the liver, and subcutaneous and visceral fat in 2002–2005 (n=275; 'ultrasound subcohort'). Results: Follow-up data (median: 15 years) was acquired for 76%. The incidence rate of T2D was significantly higher in FCHL patients compared with spouses (19.2 per 1000 person-years vs 2.8 per 1000 person-years; HR : 6.3, 95% CI: 2.4 to 16.8), whereas no differences were observed between unaffected relatives and spouses (HR: 0.9, 95% CI: 0.3 to 2.6). Cox's proportional hazard regression analyses showed that baseline HOMA2-IR and FLI≥60, but not waist circumference, BMI, or the FCHL affected state, were independently associated with incident T2D. Similar results were obtained in the ultrasound subcohort (median follow-up: 11 years), in which baseline HOMA2-IR and fatty liver (assessed by ultrasound) were independently associated with incident T2D. Conclusion: This study further corroborates the suggestion that the liver plays a central role in the pathogenesis of cardiometabolic complications in FCHL. It supports periodical screening for T2D in this high-risk population.